Peran Kepala Desa dalam Pembangunan di Desa Banjarbendo Kecamatan Sidoarjo - Auly, Laveda Nur; Agustina, Isna Fitria (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
This research aims to provide an in-depth analysis of the role of the village head in the development process in Banjarbendo Village, Sidoarjo District. The research method used is descriptive qualitative, where data is collected through several techniques, namely direct interviews with relevant parties, observation of development activities, and literature studies to strengthen the findings. The main focus of this research is to understand the extent to which the village head plays a role in driving development aimed at improving community welfare and advancing Banjarbendo Village, both from physical aspects such as infrastructure and non-physical aspects such as health. The research findings show that the role of the village head has not been effective due to several obstacles, especially related to unfinished development projects. Both physical and non-physical development have experienced delays, one of which is influenced by the slow flow of funds from the government, thus hampering the achievement of overall village development goals and the lack of innovation in development in the health sector because it is still in the stage of development and monitoring through posyandu cadres